Evaluation of glyphosate levels in sediments of milky stork foraging areas in Kuala Gula Bird Sanctuary, Perak, Malaysia - Abdul Rahman, Mohd Faid; Ismail, Ahmad; Yusof, Shahrizad; Mazlan, Norida; Engku Ariff, Engku Ahmad Khairi (Universiti Putra Malaysia Press, 2019)
Glyphosate is the most widely used herbicide in the world since its first introduction in the 1970s. Although its accumulation and direct impact on top predators are unlikely, it has the potential to affect the lower trophic community causing imbalance to the local food web. This paper highlights the background levels of glyphosate in the sediment in a part of the Important Bird and Biodiversity Programme Areas (IBA) in the Matang coast i.e., the Kuala Gula Bird Sanctuary, Perak, Malaysia. Despite housing endangered species like the milky stork and migratory birds, the area is surrounded by massive oil palm plantations that utilize glyphosate-based herbicide. Sediment samples were taken from areas frequently visited by the bird population. The herbicide was analyzed by HPLC-UV detection with previous derivatization using 9-fluorenylmethylchloroformate (FMOC-Cl). In general, the glyphosate levels were between 0.26 and 1.72 ppm. These levels are considered low when compared to other agricultural sites in both local and regional areas. In addition, no significant relationship was established between glyphosate levels in the study sites with the distance from nearby agricultural activity (r = 0.2, n = 18, p > 0.05). This evidence suggests that the pollutant most likely comes from an inter-connected network of water canals and water-bodies that accumulate the plantations’effluent over time. Due to its resistant nature and low concentration in the field, there is little concern over its adverse impact on the aquatic ecosystem in the study area. However, continuous monitoring is still emphasized in this paper.